Soil Cutting by a Chisel Plough with Self-Oscillations: Process Analysis. Issue 1 (April 2021) - Zaripova, N A; Soyunov, A S; Algazin, D N; Kulaeva, A G; Kuzmin, D E
Abstract: The paper presents the results of analytical studies. It describes the basics of modeling the chisel plough and soil interaction; it further analyzes the hypothesis of how soil is deformed. To reduce the draught of the implement, the authors propose using elastic cutter mounts to induce self-oscillations. The paper derives the amplitude of such oscillations expressed in terms of the cutter tilt angle α(t) and the moment of all forces acting on the cutter on the soil side.